Repression of the iron exporter ferroportin may contribute to hepatocyte iron overload in individuals with type 2 diabetes - Ruiyue Qiu; Kristina Alikhanyan; Nadine Volk; Oriana Marques; Christina Mertens; Anand Ruban Agarvas; Sanjana Singh; Rainer Pepperkok; Sandro Altamura; Martina U. Muckenthaler (Elsevier, 2022)
Objective: Hyperferremia and hyperferritinemia are observed in patients and disease models of type 2 diabetes mellitus (T2DM). Likewise, patients with genetic iron overload diseases develop diabetes, suggesting a tight link between iron metabolism and diabetes. The liver controls systemic iron homeostasis and is a central organ for T2DM. Here, we investigate how the control of iron metabolism in hepatocytes is affected by T2DM. Methods: Perls Prussian blue staining was applied to analyze iron distribution in liver biopsies of T2DM patients. To identify molecular mechanisms underlying hepatocyte iron accumulation we established cellular models of insulin resistance by treatment with palmitate and insulin. Results: We show that a subset of T2DM patients accumulates iron in hepatocytes, a finding mirrored in a hepatocyte model of insulin resistance. Iron accumulation can be explained by the repression of the iron exporter ferroportin upon palmitate and/or insulin treatment. While during palmitate treatment the activation of the iron regulatory hormone hepcidin may contribute to reducing ferroportin protein levels in a cell-autonomous manner, insulin treatment decreases ferroportin transcription via the PI3K/AKT and Ras/Raf/MEK/ERK signaling pathways. Conclusion: Repression of ferroportin at the transcriptional and post-transcriptional level may contribute to iron accumulation in hepatocytes observed in a subset of patients with T2DM.